PENGARUH PENGETAHUAN PAJAK, MENTAL ACCOUNTING DAN KEADILAN DISTRIBUTIF TERHADAP KEPATUHAN PAJAK UMKM - Rahadi Nugroho; Qisthon Ad; Hanik Susilawati Muamarah (SUBSTANSI, 2021)
Tax collection of SME in Indonesia have not been as enormous as their contribution in national economy. Their unsatisfactory contribution is appointed to some factors. This research aims to investigate the effect of knowledge of taxation, mental accounting, and distributive equity to tax compliance. Employing primary data taken from quessionnare distributed to SME in Pondok Aren Tax Office, this research found that knowledge of taxation, mental accounting and distributive equity have significant impact on tax compliance